Relationship between Plasma Atherogenic Index and Degreeof Stenosis in Stable Coronary Heart Disease Patients in Hospital M. Djamil Padang Hospital in 2021-2022 - Nadia Nurisma; Prima Adelin; Dina Lydia (PT. Anagata Sembagi Education, 2025)
Background: Dyslipidemia is the main risk factor for CHD besides other factors. Dyslipidemia is a lipid metabolism disorder characterized by increased total cholesterol levels, increased triglyceride levels, increased LDL levels, and decreased HDL cholesterol levels. Lipid profile ratios are an alternative to routine tests such as the plasma atherogenic index (IAP) to assess the severity of coronary heart disease. Objective: To determine the relationship between the Plasma Atherogenic Index (IAP) value and the degree of stenosis in patients with stable coronary heart disease at the M. Djamil Hospital in Padang in 2021- 2022. Methods: The scope of this research is heart disease and clinical pathology. The research was conducted in April- May 2024. The type of research is descriptive. The population covered in the study were all patients with stable coronary heart disease at the M. Djamil Hospital in Padang in 2021-2022 with a diagnosis of stable angina pectoris, a total of 54 samples using the sequential sampling technique. Univariate data analysis is presented in the form of a frequency distribution and bivariate analysis using the chi-square test, data processing using the computerized SPSS program IBM version 25.0. Results: The highest age was middle adulthood, namely 34 people (63.0%), the highest family history was none, namely 34 people (63.0%), the highest plasma atherogenic index was moderate, namely 30 people (55.6%), the degree Most stenosis was low- moderate, namely 34 people (63.0%) and there was a relationship between the Plasma Atherogenic Index (IAP) and the degree of stenosis in CHD patients at RSUP Dr. M. Djamil Padang in 2021-2022 (p=0.000). Conclusion: It is proven that there is a relationship between the Plasma Atherogenic Index (IAP) and the degree of stenosis in CHD patients at RSUP Dr. M. Djamil Padang in 2021- 2022.